Ayurveda View of Marma Sharira – A Conceptual Study - Trivedi, Ashvini; Chaudhary , Yashpal (International Research Journal of Ayurveda & Yoga, 2025)
Marma, an Ayurvedic concept, offers a distinctive and comprehensive view of human anatomy. Marma is regarded as the seats of Prana (life force) and is defined as the critical areas where Mamsa (muscle), Sira (blood vessels), Snayu (ligaments/tendons), Asthi (bones), and Sandhi (joints) connect. One hundred and seven Marmas are described in ancient books, especially the Sushruta Samhita, and are categorized according to their dimensions, structure, and the therapeutic impact of their injuries. These critical areas were crucial for prognosis, martial arts, warfare, and trauma assessment in addition to surgery. Damage to Marmas may result in deformity, discomfort, incapacity, or even death. Researchers have connected Marmas to contemporary musculoskeletal and neurovascular structures in recent decades, connecting Ayurveda with contemporary medical sciences. In addition, Marma Chikitsa’s therapeutic use is becoming more and more relevant in integrative medicine, especially in the areas of pain relief, rehabilitation, and overall wellness. This review examines Marma Sharira’s Ayurvedic roots, anatomical relationships, therapeutic value, and incorporation into contemporary anatomy and medicine.